2015
DOI: 10.1002/mbo3.254
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of structural and sequence variation within isotype lineages of the Neisseria meningitidis transferrin receptor system

Abstract: Neisseria meningitidis inhabits the human upper respiratory tract and is an important cause of sepsis and meningitis. A surface receptor comprised of transferrin-binding proteins A and B (TbpA and TbpB), is responsible for acquiring iron from host transferrin. Sequence and immunological diversity divides TbpBs into two distinct lineages; isotype I and isotype II. Two representative isotype I and II strains, B16B6 and M982, differ in their dependence on TbpB for in vitro growth on exogenous transferrin. The cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
(71 reference statements)
1
9
0
Order By: Relevance
“…Phylogenetic analysis of TbpA and TbpB sequences from N. meningitidis and N. gonorrhoeae have demonstrated that the gonococcal diversity exists predominantly as either one subset (TbpA) or two subsets (TbpB) of the isotype II-type meningococcal diversity (Figure 3). When compared at the same scale, TbpB contains substantially more variability than does TbpA within each isotype, however the isotype distinction appears in both TbpA and TbpB sequences, with strains appearing to be consistently isotype I or isotype II, as previously reported (40).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Phylogenetic analysis of TbpA and TbpB sequences from N. meningitidis and N. gonorrhoeae have demonstrated that the gonococcal diversity exists predominantly as either one subset (TbpA) or two subsets (TbpB) of the isotype II-type meningococcal diversity (Figure 3). When compared at the same scale, TbpB contains substantially more variability than does TbpA within each isotype, however the isotype distinction appears in both TbpA and TbpB sequences, with strains appearing to be consistently isotype I or isotype II, as previously reported (40).…”
Section: Resultssupporting
confidence: 73%
“…The sequences of the chosen TbpA loops were compared across a collection of three N. gonorrhoeae strains (Figure 4, bottom three sequences) and eight N. meningitidis strains (Figure 4, top eight sequences) selected to represent the overall diversity of Neisseria TbpAs (as seen in Figure 3). The overall sequence diversity of TbpA parallels the sequence diversity of the TbpB C-lobe, which divides the C-lobe variants into an isotype I cluster with a smaller size C-lobe (also reflected in the overall TbpB size) and a larger size isotype II C-lobe (40). Thus, the N. meningitidis collection included six strains expressing isotype II TbpBs and two strains expressing isotype I TbpBs (B16B6 and 90/18311) while all three N. gonorrhoeae strains expressed isotype II TbpBs.…”
Section: Resultsmentioning
confidence: 99%
“…Table below lists the accession numbers for all Slam-dependent SLP structures deposited to the Protein Data Bank (PDB). Primary references for TbpB (Moraes et al, 2009 ; Calmettes et al, 2011 , 2012 ; Noinaj et al, 2012 ; Adamiak et al, 2015 ; Frandoloso et al, 2015 ), LbpB N-lobe (Arutyunova et al, 2012 ; Brooks et al, 2014 ), HpuA (Wong et al, 2015 ), and fHbp (Cantini et al, 2009 ; Schneider et al, 2009 ; Cendron et al, 2011 ; Scarselli et al, 2011 ; Johnson et al, 2012 ; Konar et al, 2015 ) structures are also included.…”
Section: Resultsmentioning
confidence: 99%
“…The original "loopless C-lobe" (21) was derived from the N. meningitidis TbpB from strain M982 in which the larger loop regions not resolved in the crystal structure (loop 20 413−439 , loop 21 444−474 , loop 23 499−520 , loop 31 657−676 ) (34) were replaced with equivalent short linking regions identified in the structure of an Actinobacillus pleuropneumoniae TbpB (35). Two variants of the original LCL were prepared which involved the replacement of a segment of the handle domain (LCLv2) or loop 31 (LCLv3) were derived from the TbpB from N. meningitidis strain B16B6 (36) to generate a more cross-protective scaffold when used in experiments with N. meningitidis. The M982 LCL with the loop region derived from the B16B6 TbpB (loop 31 657−676 ), LCLv3, was used as the starting scaffold for hosting the loops from A. baumannii ZnuD and is localized to insertion site 4 (Figure 2).…”
Section: Computational Modeling Loop Selection and Design Of Hybridmentioning
confidence: 99%